Granule-based immobilization and activity enhancement of anammox biomass via PVA/CS and PVA/CS/Fe gel beads. (August 2020) - Wang, Jinxing; Liang, Jidong; Sun, Li; Li, Gaigai; Temmink, Hardy; Rijnaarts, Huub.H.M.
Highlights: PVA/CS and PVA/CS/Fe assists in anammox biomass immobilization and improves NRR. EPS entangles anammox cells within the gel beads, resulting in compact aggregates. The interaction between Fe and EPS strongly promotes the granule compactness. Abstract: Granule-based immobilization of anammox biomass assisted by polyvinyl alcohol/chitosan (PVA/CS) and PVA/CS/Fe gel beads was studied, via the operation of three identical up-flow reactors (R1 without gel beads, R2 with PVA/CS, R3 with PVA/CS/Fe) for 203 days. In the end, the nitrogen removal rates (NRR) were 5.3 ± 0.4, 10.0 ± 0.3 and 13.9 ± 0.5 kg-N m −3  d −1 for R1, R2 and R3, respectively. The porous PVA/CS and PVA/CS/Fe created a suitable eco-niche for anammox bacteria to grow and attach, thus being retained in the reactor. The EPS entangles newly grown cells within the gel beads, resulting in compact aggregation. The interaction between Fe ions added to PVA/CS/Fe gel beads and negatively charged EPS groups strongly promoted granule strength and compactness. The immobilization method proposed by this study was found to effectively improve biomass retention in the reactors, which is promising for advanced anammox process applications.